2007
DOI: 10.1002/ajmg.b.30497
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of tension‐type headache: A population based twin study

Abstract: The purpose was to investigate the importance of genetic and environmental factors in tension-type headache using a genetic modeling analysis. Twins age 12-41 years old from the population based Danish Twin Registry received a validated posted questionnaire about tension-type headache and migraine. Inclusion required that both twins in a pairs replied on the questionnaire and known zygosity. Twin pairs where one or both twins had co-occurrence of migraine were excluded. Migraine significantly increases the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 29 publications
2
17
1
1
Order By: Relevance
“…Obesity is a strongly genetic trait, with heritability estimates ranging from 50 – 80% in twin studies 48. Genetic influences have also been reported for most of the pain diagnoses and symptoms examined in this study, with heritability estimates ranging from 25% for irritable bowel syndrome to 45% for fibromyalgia, and up to 68% for back pain 5, 11, 17, 38, 40, 43, 44, 51, 55.…”
Section: Discussionsupporting
confidence: 51%
“…Obesity is a strongly genetic trait, with heritability estimates ranging from 50 – 80% in twin studies 48. Genetic influences have also been reported for most of the pain diagnoses and symptoms examined in this study, with heritability estimates ranging from 25% for irritable bowel syndrome to 45% for fibromyalgia, and up to 68% for back pain 5, 11, 17, 38, 40, 43, 44, 51, 55.…”
Section: Discussionsupporting
confidence: 51%
“…IL-1β and IL-18 are typically released in response to tissue injury or pathogen infection, which has not been demonstrably implicated in cases of CTTH. However, family studies have shown that genetic factors are important in the etiology of CTTH (33). We hypothesized that genetic changes may be responsible for the observed increase in IL-1β expression observed in CTTH individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Tension-type headache has been examined in three studies (20,26,27 (migraine excluded), reporting heritability of 48% for men and 44% for women (26). The latter study is the largest, including more than 7000 pairs and is likely to be the most accurate estimate for adults.…”
Section: Headachesmentioning
confidence: 99%